ELECTROCARDIOGRAPHIC CHANGES WITH STANDARD DOSE OF MEGLUMINE ANTIMONIATE THERAPY IN CUTANEOUS LEISHMANIASIS - Tahir, Moizza; Bashir, Uzma; Ahmed, Najia; Mumtaz, Jauhar (Pakistan Armed Forces Medical Journal, 2021)
Objective: To identify electrocardiographic changes associated with parenteral meglumine antimoniate and to estimate frequency of these changes. Study Design: Prospective observational study. Place and Duration of Study: Dermatology department, Combined Military Hospital Quetta and Multan, from Apr 2018 to Feb 2019. Methodology: Total of 87 patients was recruited by consecutive sampling technique. Cases of Leishmaniasis were confirmed by Leishmania donovani bodies in smear or skin biopsy. Base line electrocardiograph was done and then repeated weekly. All patients were given 15mg/kg body weight intramuscular meglumine antimoniate (Glucantime). Any change in electrocardiograph was documented. Follow up electrocardiograph was repeated two weeks after hospital discharge. Data was analyzed using SPSS-20. Results: Changes in electrocardiograph appeared between 7-27 days mean 16 SD ± 4.58. T-wave inversion was recorded in 41 (47.12%), ST elevation in 1 (1.14%), prolonged QT interval in 1 (1.14%). Meglumine antimoniate therapy was discontinued after ECG change for 5 ± SD 3 days of therapy. Follow up electrocardiograph two weeks after hospital discharge was normal. Conclusion: Early repolarization defects of T wave inversion and ST segment deviation were found with standard doses of meglumine antimoniate therapy.